Prolonged bihemispheric alterations in unfolded protein response related gene expression after experimental stroke - Rissanen, Anna; Sivenius, Juhani; Jolkkonen, Jukka (My University, 2006)
After ischemia, endoplasmic reticulum (ER) stress pathways are activated that include unfolded protein response (UPR) and protein synthesis inhibition (PSI). Both of these mechanisms aim to restore ER functioning mainly by inhibition of translation and increased processing of excess proteins in ER. We were interested in the role of these pathways during spontaneous recovery after transient middle cerebral artery occlusion (MCAO) in rats. The spontaneous recovery of rats was assessed with a limb-placing test. The expression of ER-stress-related genes (IRE1, ATF6, GRP78, eif2α, ATF4, PERK) was studied by using in situ hybridization in different brain areas on post-operative days 2, 7, 14 and 28. Elevated signals were detected in striatum contralateral to the lesion on days 2 (PERK and IRE1) and 14 post-ischemia (IRE1). Gene expression was elevated on day 7 in the striatum ipsilateral to the lesion (ATF6 and GRP78) and on day 14 (GRP78) post-ischemia. Furthermore, elevated levels of GRP78 were detected on day 14 after ischemia in the ipsilateral sensorimotor cortex. These results suggest that altered gene expression related to unfolded protein response may be more long lasting than expected following focal cerebral ischemia. In addition, these results show that the response to ER stress differs ipsi- and contralaterally after MCAO in rats. Since these differences are detected in both hemispheres only in areas adjacent to the lesion, UPR may contribute to spontaneous recovery after MCAO in rats.
Keywords: middle cerebral artery; occlusion (MCAO); gene expression; spontaneous functional recovery; unfolded protein response; endoplasmic reticulum; striatum